Single-Polarization Single-Mode Hollow-Core Anti-Resonant Fiber with Low Loss and Wide Bandwidth - Yong You; Wei Liu; Shuo Zhang; Jianxiong Wu; Yuanjiang Li; Huimin Shi; Haokun Yang (Photonics)
Stable generation and propagation of single-polarization single-mode (SPSM) beams in hollow-core fiber (HCF) has become an important research direction. However, their routine use is yet to become a reality, a major obstacle is to maintain the polarization state of light at a sufficiently long transmission distance in a wide spectral range. In the paper, a hollow-core anti-resonant fiber (HC-ARF) that can support SPSM beam transmission with an average loss of 15 dB/km in wavelengths beyond 1000 nm is proposed. SPSM guidance is achieved by setting the cladding tubes in the orthogonal direction to have different structures and material properties. Different cladding tube structures break the degeneracy of polarization modes, and different cladding tube materials make the polarization modes experience enough loss difference. In the range of more than 600 nm, the y-polarization loss ≈ 9.3 dB/km, while the x-polarization is > 500 dB/km, and the birefringence is > 1.7 × 10−5. In addition, the SPSM optimization process and bending losses in different directions are also discussed in detail.